Identification of Work Stress Levels on New Nurses - Pakaya, Nasrun; Dulahu, Wirda Y (GLOBAL HEALTH SCIENCE GROUP, 2024)
Reality Shock is a phenomenon that appears in new nurses as a result of a reaction to self-expectations when in a new work situation, which requires time to adapt well to the work environment, to deal with conflicts that will occur in the work environment. When entering a new work environment, nurses are faced with various problems including a lack of confidence in providing nursing care, an inability to think critically, and a lack of clinical ability. Job stress will reduce the performance of nurses, if this happens over a long period it will cause nurses to experience turnover intention. Based on the above, the researchers identified the level of work stress on new nurses which is the basis of research to minimize stress levels and improve the performance of new nurses. The method in this study is a survey in the form of a questionnaire to new nurses who work in 4 government agencies in Gorontalo Province. The number of respondents in this study was 98 respondents which was taken by the total sampling method. The results showed that most of the new nurses experienced work stress in the heavy category, namely 67 respondents (68.4%) while the nurses with mild work stress category were 31 people (31.6%). Based on this research, it can be concluded that new nurses are vulnerable to work stress, so it is hoped that a new nurse coaching program is needed to minimize the incidence of work stress.